The study of modern culture through semiotic analysis - Abikenov, Zh.O.; Kudaibergenov, S.E. (KU Publ., 2022)
The article’s methodological foundation is the cultural principles of semiotics, the study of any phenomenon in its development. It defines the interaction between semiotics and culture through symbols, shows the relationship between semiotics and culture, and discusses the importance of different levels, semiosphere, semiotic space, and so on. This allows us to deepen our understanding of the cultural space and recognize human culture in its essence. Modern culture, which manifests itself in various forms, such as hyper semiotics, hyperrealism, and hypermodernism, reflects the development of different communities in our society, and thus different rules of the game have also emerged. An important problem in hypersemiotics is the excessive use of symptoms in modern life. This is expressed in many characteristics: changing signs, immanent principle, difference, conditional language games, modeling, and break. Therefore, the study of the philosophy of symbols in modern culture is a necessity to deepen our understanding of semiotic research. This conclusion is confirmed by the study of modern culture, the discussion of semiotics of modern culture, which uses the structure of symbols in the form of icons, signs and symbols to abstract the meaning of life. Semiotics is considered as a method of studying modern culture and analyzed from the point of view of its attitude to culture as a whole.
Семиотикалық талдау арқылы қазіргі мәдениетті зерттеу
Изучение современной культуры через семиотический анализ
Keywords: semiotica; hypertextuality; hypersemiotics; hyperreality; hypermodernism; cultural; modern; research; method; specifically